Bertiella anapolytica Baylis, 1934 (Cestoda, Anoplocephalidae) in Rattus spp.: morphology, distribution and evolutionary history - Haukisalmi, Voitto; Ribas, Alexis; Morand, Serge (Folia parasitologica, 2025)
The present study describes the morphology and phylogenetic position of two specimens of Bertiella Stiles et Hassall, 1902 (Cestoda, Anoplocephalidae) from Rattus tanezumi (Temminck) (Muridae) from Đồng Tháp Province in southern Vietnam. The phylogenetic analysis was based on sequences of the large subunit ribosomal RNA gene (28S). The specimens were described and shown to be morphologically similar to Bertiella anapolytica Baylis, 1934 from Rattus spp. from Indonesia (Sumatra, type locality) and Australia, except for a few quantitative differences. The identification was confirmed by the phylogenetic analysis, which showed a strong affinity and fairly limited genetic divergence between the specimens from Vietnam and Australia. This is the first verified case of Bertiella in murid rodents from continental Eurasia. The uterine pore and associated canal present in the posterolateral corners of gravid proglottids of B. anapolytica are considered to form a true, functional structure used for egg release prior to apolysis. The phylogenetic analysis suggested that B. anapolytica has diverged as a consequence of a shift from marsupials, which probably took place east of the Wallace's line, either in Wallacea or Australasia. The presence of B. anapolytica west of the Wallace's line (Vietnam, Sumatra), where marsupials are absent, may be explained by a westward dispersal in commensal rats, possibly Rattus exulans (Peale), a species transported throughout the Pacific and South-East Asia by prehistoric people.
Keywords: 28S; Cestode Infections; Phylogeny; Biological Evolution; rodents; krysa rodu Rattus; zvířata; Cyclophyllidea; fylogeneze; biologická evoluce; cestodózy; Muridae; Vietnam; nemoci hlodavců; Rats; phylogeny; Cestoda; Animals; Austrálie; Rodent Diseases; Australia; RNA, Ribosomal, 28S; RNA ribozomální 28S